2015
DOI: 10.1111/omi.12094
|View full text |Cite
|
Sign up to set email alerts
|

TRIB3 mediates the expression of Wnt5a and activation of nuclear factor‐κB in Porphyromonas endodontalis lipopolysaccharide‐treated osteoblasts

Abstract: Porphyromonas endodontalis lipopolysaccharide (LPS) is considered to be correlated with the progression of bone resorption in periodontal and periapical diseases. Wnt5a has recently been implicated in inflammatory processes, but its role is unclear as a P. endodontalis LPS-induced mediator in osteoblasts. Tribbles homolog 3 (TRIB3) encodes a pseudokinase and has been linked to inflammation in certain situations. Here, we found that P. endodontalis LPS induced Wnt5a expression in a dose- and time-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…Taken together, these data indicate that SIRT1 is a negative regulator for NF-κB transcriptional activity. A previous study indicated that P.e LPS induces the expressions of M-CSF, Wnt5a, and IL-6 through promoting the transcriptional activity of NF-κB in MCET3-E1 cells [16,17,43]. In order to study whether NF-κB is also involved in the expression of MMP-13 in P.e LPS–induced osteoblasts, the cells were pretreated with NF-κB inhibitor Bay 11-7082.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data indicate that SIRT1 is a negative regulator for NF-κB transcriptional activity. A previous study indicated that P.e LPS induces the expressions of M-CSF, Wnt5a, and IL-6 through promoting the transcriptional activity of NF-κB in MCET3-E1 cells [16,17,43]. In order to study whether NF-κB is also involved in the expression of MMP-13 in P.e LPS–induced osteoblasts, the cells were pretreated with NF-κB inhibitor Bay 11-7082.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is the main constituent of the outer membrane of P.e ; it is an important initiating factor for periapical inflammatory reaction and bone destruction [13]. A previous study in a mouse model indicated that P.e LPS is a pivotal inducer for bone resorption [14] and for the expression of numerous inflammatory mediators, including interleukin (IL)-6, macrophage colony stimulating factor (M-CSF), and Wnt5a in osteoblasts [15–17]. However, there has been little information about the role of P.e LPS in MMP-13 expression in osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that P. endodontalis LPS stimulated NF-kB translocation and activation in SH-9 cells accompanied by IkB phosphorylation and degradation, followed by the expression of IL-23. Our previous studies demonstrated that the NF-kB signaling pathway is important in the expression of cluster of differentiation 14, Toll-like receptor (TLR)-2, TLR-4, RANKL, IL-6, IL-34 and IL-1β in P. endodontalis LPS-treated osteoblasts (5,32,33). In the present study, pretreatment with an NF-kB inhibitor decreased the P. endodontalis LPS-induced expression of IL-23 to basal levels, indicating that the NF-kB signaling pathway was closely associated with IL-23 expression in PDL cells in response to P. endodontalis LPS.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that wnt5a mRNA is upregulated in the gingiva of patients with periodontitis (Nanbara et al., ) and a genome‐wide association study found suggestive evidence of association for the wnt5a gene and severe periodontitis (Divaris et al., ). The evolutionary conserved sFRP5 and wnt5a system has increasingly gained attention in the research field of periodontitis over the last years (Divaris et al., ; Hu et al., ; Lee et al., ; Nanbara et al., ; Xu et al., ; Yu et al., ; Zhou, Dorfer, Chen, & Fawzy El‐Sayed, ). Recently, a reciprocal relationship between sFRP5 and wnt5a expression in periodontal health and disease , as well as that sFRP5 could block experimental periodontal inflammation in vivo , was demonstrated (Maekawa et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary conserved sFRP5 and wnt5a system has increasingly gained attention in the research field of periodontitis over the last years (Divaris et al, 2013;Hu et al, 2016;Lee et al, 2016;Nanbara et al, 2012;Xu et al, 2015;Yu et al, 2015;Zhou, Dorfer, Chen, & Fawzy El-Sayed, 2017). Recently, a reciprocal relationship between sFRP5 and wnt5a expression in periodontal health and disease, as well as that sFRP5 could block experimental periodontal inflammation in vivo, was demonstrated (Maekawa et al, 2017).…”
mentioning
confidence: 99%